2015
DOI: 10.1007/s12560-015-9207-3
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A and E Viruses in Wastewaters, in River Waters, and in Bivalve Molluscs in Italy

Abstract: Several studies have reported the detection of hepatitis A (HAV) and E (HEV) virus in sewage waters, indicating a possibility of contamination of aquatic environments. The objective of the present study was to assess the occurrence of HAV and HEV in different water environments, following the route of contamination from raw sewage through treated effluent to the surface waters receiving wastewater discharges . Bivalve molluscan shellfish samples were also analyzed, as sentinel of marine pollution. Samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 38 publications
3
40
0
Order By: Relevance
“…This hypothesis is supported by studies that found HEV RNA in surface water in proximity of pig farms [170,171]. HEV sequences similar to sequences found in patients with autochthonous hepatitis E infection and in swine have also been repeatedly found in river and seawater [172,173,174]. In addition, some of the shellfish found to be HEV RNA positive in Scotland were harvested near a slaughterhouse and pork processing plant [118].…”
Section: Transmission Pathways Of Zoonotic Hevmentioning
confidence: 77%
“…This hypothesis is supported by studies that found HEV RNA in surface water in proximity of pig farms [170,171]. HEV sequences similar to sequences found in patients with autochthonous hepatitis E infection and in swine have also been repeatedly found in river and seawater [172,173,174]. In addition, some of the shellfish found to be HEV RNA positive in Scotland were harvested near a slaughterhouse and pork processing plant [118].…”
Section: Transmission Pathways Of Zoonotic Hevmentioning
confidence: 77%
“…In fact, the identity with other Slovenian swine HEV isolates in the area was 100%. The virus was also detected in a river sample in Italy [214] and the Netherlands [215]. …”
Section: Hev In Environment and Foodmentioning
confidence: 99%
“…Indeed, the presence of HEV has been demonstrated in several studies performed in environmental water, river and wastewater samples in America, Asia and Europe [1115]. …”
Section: Introductionmentioning
confidence: 99%